1989
DOI: 10.1136/bmj.299.6693.228
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of maternal diet during lactation and use of formula feeds on development of atopic eczema in high risk infants.

Abstract: 10 Centers for Disease Control. Classification system for httman T-lymphotropic virus type III/lvmphadenopathy-associated virus infections. MMWR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0
2

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(112 citation statements)
references
References 10 publications
3
107
0
2
Order By: Relevance
“…Despite the availability of modern infant formulae, exclusive breast-fed infants are healthier than formula-fed infants in all countries, even industrialized ones. These data have been reviewed (Chandra 1979(Chandra ,1991(Chandra ,1997(Chandra ,2000Chandra et al, 1989;Saarinen & Kajosaari, 1995).…”
Section: Breast Feedingmentioning
confidence: 99%
“…Despite the availability of modern infant formulae, exclusive breast-fed infants are healthier than formula-fed infants in all countries, even industrialized ones. These data have been reviewed (Chandra 1979(Chandra ,1991(Chandra ,1997(Chandra ,2000Chandra et al, 1989;Saarinen & Kajosaari, 1995).…”
Section: Breast Feedingmentioning
confidence: 99%
“…So, although it appears that breast feeding may reduce the incidence of allergy during early childhood (Chandra et al 1989;Morris, 1991), this protection seems t9 be lost at about 9 years of age (Poysa et al 1989(Poysa et al , 1991. This theory was supported by Aberg et al…”
Section: H U M a N Milk As A Protection A G A I N S T Allergymentioning
confidence: 99%
“…In an ambitious study undertaken by Chandra et al (1989), mothers who were breast feeding their infants (n = 97) were randomly allocated to a restricted diet group avoiding milk, dairy products, eggs, fish, peanuts and soya (n = 48), or an unrestricted diet group (n = 49). Mothers who bottle fed their infants (n = 124) were directed to use cows' milk formula or soya formula or a casein hydrolysate.…”
Section: A T E R N a L E L I M I N A T I O N D I E T S D U R I N G mentioning
confidence: 99%
“…However, at 10 years of age the rates of allergies were the same between the children in both groups. 59,60 A meta-analysis of these studies concluded that a food allergen avoidance diet of the mothers during lactation may transiently reduce the development of eczema in early childhood. 50 The authors also noted that methodological limitations of the reported studies suggest caution before implementing the findings.…”
Section: Intervention Strategy During Breastfeeding For the Mothermentioning
confidence: 99%
“…43,57 Some studies have therefore evaluated the utility of maternal food allergen avoidance diets during lactation for preventing atopic disease in high-risk infants. [58][59][60] Two prospective controlled studies evaluated whether maternal diet for the first 3 months of lactation and avoidance of soy and peanuts for the entire lactation period affected atopy in high-risk infants placed on a relatively hypoallergenic dietary regimen during infancy. These studies noted significant reductions of atopic eczema in the maternal diet groups by ages 3, 6 and 18 months.…”
Section: Intervention Strategy During Breastfeeding For the Mothermentioning
confidence: 99%